(3a+7)+(2a-6)=(-9)

Simple and best practice solution for (3a+7)+(2a-6)=(-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3a+7)+(2a-6)=(-9) equation:


Simplifying
(3a + 7) + (2a + -6) = (-9)

Reorder the terms:
(7 + 3a) + (2a + -6) = (-9)

Remove parenthesis around (7 + 3a)
7 + 3a + (2a + -6) = (-9)

Reorder the terms:
7 + 3a + (-6 + 2a) = (-9)

Remove parenthesis around (-6 + 2a)
7 + 3a + -6 + 2a = (-9)

Reorder the terms:
7 + -6 + 3a + 2a = (-9)

Combine like terms: 7 + -6 = 1
1 + 3a + 2a = (-9)

Combine like terms: 3a + 2a = 5a
1 + 5a = (-9)
1 + 5a = -9

Solving
1 + 5a = -9

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + 5a = -9 + -1

Combine like terms: 1 + -1 = 0
0 + 5a = -9 + -1
5a = -9 + -1

Combine like terms: -9 + -1 = -10
5a = -10

Divide each side by '5'.
a = -2

Simplifying
a = -2

See similar equations:

| 2(-5+v)=-4 | | v^2+14v=19 | | -8=-6x-3 | | 17=w | | 12=4+6m | | G(x)=3f(x-2)-4 | | 7T+2=12+5T | | 12=10x+2x | | -2(6n-8)=16-12n | | 4k+7=-4 | | 7K+-8K+-5K= | | 8x-2=-9+nx | | x-.55x=0 | | 1=-15+8x | | 12=1.5 | | 2(3x-5)=9-(2x-5) | | 0.2x-6=x | | 2(5d+3)=4d | | -5.6+12.2=5h | | 4(m-3)=-32 | | 4x+6x+1=0 | | x^2-5=sqrt(3*x) | | -23-2p=19-p | | 12x^2+35x-3=0 | | 7=9(2f+5) | | 3(2x+3)=4-x | | 4w-7=3w+1 | | x^2+18x+30=0 | | 4x-5=4x-9 | | 1/2n+5/6=2/3 | | (6x+2)+20=90 | | -8-7x-6x=-8 |

Equations solver categories